ORGANIZATION OF EDUCATIONAL COOPERATION IN A DIGITAL EDUCATIONAL ENVIRONMENT IN MATHEMATICS LESSONS IN PRIMARY SCHOOL - Kokhanovska, Olena; Dovgij, Oleg (Mountain School of Ukrainian Carpaty, 2022)
For students to successfully master mathematics in the conditions of a digital educational environment, it is important to create conditions that would promote an increase in the interest in learning of students of primary education and ensure the development of their abilities and key competencies in the learning process. The article examines the essence, content and forms of educational cooperation in remote mathematics lessons in elementary school with the help of digital applications. It is emphasized the need to use digital technologies both in the process of developing digital literacy of teachers and in the context of organizing digital cooperation between teachers and younger students in the context of using ICT tools and creating conditions for their integration into the educational process. The requirements of the Concept of the New Ukrainian School regarding the mathematical competence of lower grade students were considered. The essence of the key concepts of the research is analyzed. The principles of cooperative learning are highlighted. It was noted that the main idea of cooperative learning is to learn together, and not just to perform together. The technology of preparing and conducting a mathematics lesson using the remote form of learning in cooperation based on small groups is described. Some forms of organizing collaborative learning in remote mathematics lessons based on small groups and digital means of their implementation are outlined. Special mathematical websites and applications are presented that can significantly motivate students to solve mathematical problems, visualize content and develop key competencies of students. It was concluded that the organization of educational cooperation in a digital educational environment in mathematics lessons in elementary school involves such interaction between the teacher and students, students among themselves in the educational situation, during which the children's established methods of action are restructured, the components of educational activity are formed (that is, formed learning ability). Keywords: cooperation, educational cooperation, digital educational environment, digital applications, students of lower grades, mathematics.